DOES ECONOMIC POLICY UNCERTAINTY REDUCE FINANCIAL INCLUSION? (International Journal of Banking and Finance, 2021)
This study investigates whether the level of economic policy uncertainty (EPU) would reduce the level of financial inclusion. It was predicted that a high level of EPU could have a negative effect on the level of financial inclusion. It was argued that a high level of EPU would discourage financial institutions from providing basic financial services to low end customers and unbanked adults, and this would lead to a decrease in the level of financial inclusion. Using a sample of 22 countries, the study found that the level of EPU did not have a significant impact on financial inclusion. None of the nine indicators of financial inclusion were found to have a significant direct relationship with EPU. However, there was some evidence that the combined effect of a high level of EPU and high nonperforming loans could reduce financial inclusion, particularly through bank branch contraction and a reduction in the use of electronic payments. Furthermore, the use of formal accounts and credit cards would increase in times of high credit supply and when there was a high level of EPU.